Problem Solving Therapy for Home-Hospice Caregivers: A Pilot Study. Issue 4 (1st October 2020) - Gregory, Christin; Gellis, Zvi
Abstract: This pilot study examined the effects of Brief Problem-Solving Therapy on caregiver quality of life, depression, and problem-solving in family caregivers of hospice patients. Thirty-seven family caregivers to home-based hospice patients (mean age 62.8 [SD = 12.32]) were randomized to the study group (PST-Hospice), for a 45 minute per week/5 week intervention or comparison group of usual care plus caregiver education (UC + CE). The severity of depressive symptoms, caregiver quality of life and problem-solving functioning were assessed at baseline and follow-up. At post-test, the PST-Hospice condition had significantly higher scores on caregiver quality of life compared to UC + CE. On the Social Problem Solving Inventory-Revised Short Form (SPSI-R) measure, PST-Hospice scores clinically improved as compared to UC + CE on Positive Problem Orientation and Rational Problem-Solving subscales. In addition, this pilot study found that brief problem-solving treatment delivered by a hospice social worker appears to be an acceptable and feasible tool for routine use in the home-hospice setting.